2017
DOI: 10.1039/c7mh00088j
|View full text |Cite
|
Sign up to set email alerts
|

Visualising compositional heterogeneity during the scale up of multicomponent zeolite bodies

Abstract: An unprecedented approach is introduced to compositionally map binder-containing Li-X zeolite sorbents at various stages of the industrial manufacture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In our previous work using APT to study large, carefully prepared crystals of ZSM-5, the Al distribution was random in the fresh material, so finding clustered Al in the commercial material highlights the imperfections found in industrial catalysts compared to model systems 40 . This assertion is supported by the recent application of advanced microscale and nanoscale characterization techniques, which have revealed that small, industrial zeolite crystals can be quite heterogeneous, and that the results of bulk studies give an ensemble average from a diverse population of crystals 41 45 . The second needle of fresh Cu-ZSM-5, 2 , also had Cu segregation, which is reflected in the NND and RDF.…”
Section: Resultsmentioning
confidence: 91%
“…In our previous work using APT to study large, carefully prepared crystals of ZSM-5, the Al distribution was random in the fresh material, so finding clustered Al in the commercial material highlights the imperfections found in industrial catalysts compared to model systems 40 . This assertion is supported by the recent application of advanced microscale and nanoscale characterization techniques, which have revealed that small, industrial zeolite crystals can be quite heterogeneous, and that the results of bulk studies give an ensemble average from a diverse population of crystals 41 45 . The second needle of fresh Cu-ZSM-5, 2 , also had Cu segregation, which is reflected in the NND and RDF.…”
Section: Resultsmentioning
confidence: 91%
“…Examples of these techniques are UV-vis diffuse reflectance micro-spectroscopy and confocal fluorescence microscopy (CFM), 10 focused-ion-beam scanning electron microscopy (FIB-SEM), 11 X-ray tomography, 12 X-ray diffraction computed tomography (XRD-CT) 13 and NanoSIMS. 14 The combination of UV-vis micro-spectroscopy and confocal fluorescence microscopy was used to study zeolite-based extrudates. 8,15,16 However, these techniques have mainly been used to study extrudates during staining probe reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For ease of handling, postsynthetic modifications applied in the synthesis (e.g. to introduce different metals) are typically performed on the shaped bodies, which, in turn, could significantly impact on the properties and effectiveness compared with the powder catalysts. In anticipation of a potential scaleup of these materials, we thus prepared CsX g and BCsX g from binder‐free commercial NaX granules (1.6–2.5 mm in diameter) by following an equivalent procedure to that used for the zeolite powders.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Nonetheless, we note that,o nalarges cale,t hisp rocess needstobeoperated in afix-bed reactor, andtherefore,the catalystm ustb ep reparedi nt he form of millimeter-sized shaped bodies.F or ease of handling,p ostsyntheticm odificationsa ppliedint he synthesis(e.g. to introducedifferent metals)are typically performedo nthes hapedb odies, [20,21] which, in turn, coulds ignificantly impact on thep ropertiesa nd effectiveness compared with thep owderc atalysts.I na nticipationo fapotential scaleupo ft hese materials, we thus prepared CsX g and BCsX g from binder-free commercial NaX granules (1.6-2.5 mm in diameter) by following an equivalentp rocedure to that used fort he zeolite powders. Additionally,t oi nvestigatet he possibility of reducing the cesium content,amilder exchange procedure was applied, leadingt oB Cs L X g .F ull details of the synthesis are provided in the Experimental Section.…”
Section: Preparation and Evaluationo Freference Catalystsmentioning
confidence: 99%